(untitled) (Romano džaniben, 2008)
Lorenz Aggermann, Eduard Freudmann, Can Gülcü / Beograd Gazela Devla, Devla! Anna Rezková / Oáza křehkých duší Matéo Maximoff / Sudba Ursitorů Andrzej Polakowski / Požegnanie taboru. Fotografie 1967 Rombase Romlex Romani Project Manchester / The Romani Linguistics Page Ján Šándor / Ciglianka Erich Maria Schneller / Zigeuner. Roma. Menschen